2014
DOI: 10.1108/bfj-02-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of ISO-22000 in Spain: obstacles and key benefits

Abstract: Purpose – The purpose of this paper is to analyze the status of the implementation of ISO 22000 in the food industry in Spain. The study identifies the main difficulties faced by firms during the adoption process, the benefits obtained, and the most influential benefits on firms overall satisfaction with ISO 22000. Design/methodology/approach – A questionnaire was developed to identify the difficulties and benefits for ISO 22000 implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 48 publications
6
69
2
Order By: Relevance
“…The key benefits obtained by our sample companies were food safety improvement, reduction of illness and other risks arising from food, improvement of consumers' confidence, improvement of customers and stakeholders' satisfaction, followed by improvement of sales volumes. Similar findings were also obtained by Escanciano and Santos-Vijande (2014b) who mentioned better control of food hazards, continuous improvement of food safety and increased customer confidence among the benefits of ISO 22000 certification that most contribute to the fulfilment of the companies'objectives. The ISO 22000 benefits made further the subject of an exploratory factor analysis, to collect new evidence.…”
Section: Analysis Of Benefits Of the Iso 22000 Food Safety Managementsupporting
confidence: 84%
See 1 more Smart Citation
“…The key benefits obtained by our sample companies were food safety improvement, reduction of illness and other risks arising from food, improvement of consumers' confidence, improvement of customers and stakeholders' satisfaction, followed by improvement of sales volumes. Similar findings were also obtained by Escanciano and Santos-Vijande (2014b) who mentioned better control of food hazards, continuous improvement of food safety and increased customer confidence among the benefits of ISO 22000 certification that most contribute to the fulfilment of the companies'objectives. The ISO 22000 benefits made further the subject of an exploratory factor analysis, to collect new evidence.…”
Section: Analysis Of Benefits Of the Iso 22000 Food Safety Managementsupporting
confidence: 84%
“…A wide number of food borne hazards pose risks and threats to health and raise barriers to global trade in foods (Soman and Raman, 2016). The global public health challenges as well as the more stringent government regulations and the increasing demands from the customers concerning the food safety take more and more food companies to seek better and safer production systems or service delivery.Beyond complying with basic food regulations and following acceptable workplace practices, more organisations are deciding to develop a comprehensive food safety management system, which is critical to the success of the business, either it operates in food production, storage, packaging or preparation (Mensah and Julien, 2011;Escanciano and Santos-Vijande, 2014b). An efficient food safety management system helps the company to protect its competitive market place, customers and the community, guaranteeing continuous prevention of food borne illnesses, and the promotion of safe to eat foods.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of recent studies on potential incentives and barriers for the implementation of FSMSs (Escanciano & Leticia Santos‐Vijande, ; Karaman et al, ; Macheka et al, ), 29 items (reported in Table ) were identified and included in the questionnaire. The food safety/quality managers were asked to indicate their level of (dis)agreement on each of the 29 items (on a 7‐point Likert scale), ranging from 1 (“strongly disagree”) to 7 (“strongly agree”).…”
Section: Resultsmentioning
confidence: 99%
“…Cronbach's alpha was used to measure the internal consistency reliability of the measurement scale, and all the three constructs exceeded the 0.70 threshold. All the multi-item scales were based on extensive reviews of prior studies on FSMSs adoption (Escanciano & Leticia Santos-Vijande, 2014;Karaman et al, 2012;Macheka et al, 2013). Thus, the scale items have content validity.…”
Section: Incentives and Barriers For The Implementation Of Market-bmentioning
confidence: 99%
See 1 more Smart Citation